Application of Regular Grammar in the Syntactic Analysis of Email Addresses - Fandiño-Mesa, Cristian Alejandro; Suárez-Barón, Marco Javier; Jaramillo-Acevedo, César Augusto (Ingeniería, 2023)
Context: This article proposes the use of regular grammar as a strategy to validate the textual structures of emails. It focuses on the RFC 5321 standard and its syntax, formalizing regular grammars to apply production rules with the aim of validating the syntactic context of each structure of an email address. Method: This article presents a literature review and the development of an email validation model. Related texts focus on the Internet Protocol, along with building automata that apply IPV4 protocol. There are three phases: the development of the model from syntax and regular grammar rules and its construction and application. Results: The result is a functional application that validates email addresses based on regular grammars and existing regulations. When running efficiency tests, our application obtained a higher email validation margin in comparison with JFLAP. The library can work as a great analyzer of grammatical or lexical structures. Conclusions: The email validation tool based on GR regular grammars contributes to the practical use of specialized algorithms in the field of computer science, since it is possible to apply it to the recognition of search patterns such as the analysis of lexical structures (e.g., NITs, alphanumeric codes, and valid URLs).